Pengaruh Penerapan Ice Breaking terhadap Hasil Belajar Matematika pada Materi Barisan dan Deret Aritmatika Siswa Kelas X - Nurul Hasanah; Asyril Asyril (Lembaga Pengembangan Kinerja Dosen, 2025)
Low student achievement in mathematics, particularly in arithmetic sequences and series, has led to decreased learning motivation and participation. Therefore, innovative and engaging instructional strategies are required, one of which is the implementation of ice-breaking activities to reduce boredom and enhance students’ learning engagement. This study aimed to examine the effect of implementing ice breaking on the mathematics learning outcomes of tenth-grade students at SMK Kesehatan Samarinda in the topic of arithmetic sequences and series. This research employed an experimental method using a quasi-experimental design, involving two groups: an experimental group that received instruction incorporating ice breaking and a control group that did not receive such treatment. The total sample consisted of 60 students selected through purposive sampling. The research instrument was a learning achievement test administered as a pretest and posttest. Data were analyzed using a paired sample t-test to determine differences in learning outcomes between the two groups. The results revealed a significance value of 0.000 (< 0.05), indicating a significant difference in learning outcomes between the experimental and control groups. Therefore, it can be concluded that the implementation of ice breaking has a significant effect on improving students’ mathematics learning outcomes. This strategy creates a more active, interactive, and enjoyable learning environment, thereby facilitating students’ understanding of mathematical concepts, particularly arithmetic sequences and series.